看護婦のメンタルヘルスに関する研究 - 石松 直子; 大塚 邦子; 坂本 洋子 (日本看護研究学会雑誌, 2001)
In order to know the situation on nurses' current mental health, this study is planned to analyze the results of the survey on their job-stress, job-satisfaction, egogram and the correlations between the three factors above. The questionnaires to 333 nurses in the hospital "A" were recovered from 252 nurses (75.7%).The following results were obtained : 1. 72.2% of the total subjects have perceived job-stress, 50.4% having developed stress symptoms, especially aged 20-29 and 55-59 nurses have perceived than the other ages. 2. The job-satisfaction was counted 114 scores out of the total 228 (50%), especially aged 30-34 nurses who had the roles of various activities of the committee were counted lower scores than the other ages. 3. On the patterns of the egogram, N-type b,i.e. 'mother' type, was ranked as the first place, N-type' c,i.e. 'workholic' type, as the second one. On the egogram-scale 'AC', the young were counted high scores. While the more they had the roles and ages, the more their egogram-scale 'CP' and 'A'. 4. There were some significant correlations between job-stress, job-satisfaction and egogram. Stress was a possible factor to lessen job-satisfaction. Egogram was a clue to foresee possible stress development and affected on job-satisfaction. In order to improve the mental health of nurses, we found it might be useful to understand the correlations between these three factors. 看護職のメンタルヘルス対策を検討するための資料を得ることを目的として，質問紙を用いストレス・職務満足度・エゴグラムの実態と３調査相互の関連について検討した｡ 調査対象は，Ａ病院看護婦333名であり，解析対象は回答を得た252名 (75.7%) である｡ 　全対象者の72.2%がストレス発生条件をもち，50.4%がストレス状態であった｡ 特に20～29歳と55～59歳にストレス状態である者が多かった｡ 職務満足度は平均50%であり，30～34歳で委員会活動をしている者の満足度が低かった｡ エゴグラムは看護婦特有のパターンがあり，若い人はACが高く，年齢や役割が増えるとCP・Ａが高くなっていた｡ 解析の結果，ストレスは職務満足度を低減し，エゴグラムはストレスの増加を予測するてがかりとなり，また職務満足度に影響することなど，３者は相互に関連することが明らかになった｡ 　本研究結果から，看護婦のメンタルヘルス対策を考えていく上で，ストレス・職務満足度・エゴグラムから対象の特性を理解し，関わっていくことは有用であることがわかった｡